2021
DOI: 10.2147/dmso.s302207
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Different Obesity Phenotypes and Liver Fibrosis Scores in Elderly Individuals with Fatty Liver in Taiwan

Abstract: Purpose: To examine the association between different phenotypes of obesity or metabolic syndromes and liver fibrosis score in a Taiwanese elderly population with fatty liver. Patients and Methods: This cross-sectional study included 1817 participants aged ≥65 years with fatty liver diagnosed by sonography. We used ethnicity-specific criteria for body mass index and metabolic syndrome, and to define obesity phenotypes as metabolically healthy non-obese (MHNO), metabolically unhealthy non-obese (MUNO), metaboli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 55 publications
(76 reference statements)
1
3
0
Order By: Relevance
“…A study by Kuang et al (2022) demonstrated that both the metabolically healthy/abdominal obesity and metabolically unhealthy/ abdominal obesity phenotypes were closely associated with an increased risk of NAFLD in both sexes [35]. Lee The authors concluded that obesity alone has more deleterious effects than metabolic disorders on the severity of advanced fibrosis, and these effects were greater in women than in men [36]. These findings are consistent with the results of this study.…”
Section: Discussionsupporting
confidence: 87%
“…A study by Kuang et al (2022) demonstrated that both the metabolically healthy/abdominal obesity and metabolically unhealthy/ abdominal obesity phenotypes were closely associated with an increased risk of NAFLD in both sexes [35]. Lee The authors concluded that obesity alone has more deleterious effects than metabolic disorders on the severity of advanced fibrosis, and these effects were greater in women than in men [36]. These findings are consistent with the results of this study.…”
Section: Discussionsupporting
confidence: 87%
“…Nonalcoholic fatty liver disease (NAFLD) is one of the most common chronic liver disease 1 , 2 , and also an emerging risk factor for type 2 diabetes mellitus, cardiovascular disease, renal diseases and all-cause mortality 3 . The prevalence of NAFLD is reported to be approximately 25% worldwide 4 , ranges from 24.0 to 46.0% in western industrialized countries and from 7.9 to 54.0% in Asian countries 5 , 6 . As obesity is a major risk of NAFLD, the prevalence of NAFLD is expected to continue rising paralleled with the global epidemic of obesity 6 , 7 ,especially in China where obesity has increased at an estimated annual rate of 0.32%.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of NAFLD is reported to be approximately 25% worldwide 4 , ranges from 24.0 to 46.0% in western industrialized countries and from 7.9 to 54.0% in Asian countries 5 , 6 . As obesity is a major risk of NAFLD, the prevalence of NAFLD is expected to continue rising paralleled with the global epidemic of obesity 6 , 7 ,especially in China where obesity has increased at an estimated annual rate of 0.32%.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that MAFLD is closely related to obesity, and ferroptosis might further promote the development of MAFLD by affecting obesity. 39,40 Experimentally, it has been reported that iron-chelating agents (e.g. deferoxamine, deferiprone or deferasirox) have the potential to treat obesity.…”
Section: Obesitymentioning
confidence: 99%